STUDI DESKRIPTIF SELF ESTEEM PADA SISWA KELAS XI SMAN 1 MARGAASIH - Wida Rosani; Siti Fatimah; Ecep Supriatna (IKIP Siliwangi, 2021)
This study aims to describe the condition of self-esteem in class XI students of SMAN 1 Margaasih. This research is a quantitative descriptive study with a sample of 100 students from a total population of 355 students. The sampling technique used a random sampling technique and used Schiraldi's instrument (2001). In this study, it was revealed that thecondition self-esteem of class XI students of SMAN 1 Margaasih was generally in the medium category or if the percentage was 71%, while the high category was 16% and the low category was 13%. The data analyzed showed that the level of self-esteem in each category was mostly experienced by women. This can be seen from 15 students who are categorized as high, 81.25% are female students and 18.75% are male students. Then for thecategory moderate self-esteem, there are 71 students of which 70.4% are female and 29.5% are male. Meanwhile, for thecategory self-esteem low, there are 13 students of which 69.2% are female and 30.8% are male. This is because women generally have self-esteem lowerthan men, examples that appear are pessimism and lack of self-confidence or the feeling that women need to be protected. Physical conditions such as height, weight, skin color, etc. also greatly affect the formation of self-esteem students'. Keywords: : Self Esteem, Students